2016
DOI: 10.1016/j.jval.2016.09.1787
|View full text |Cite
|
Sign up to set email alerts
|

Non-Adherence to Antihypertensive Drugs: A Systematic Review and Meta-Analysis

Abstract: Background: Hypertension drives the global burden of cardiovascular disease and its prevalence is estimated to increase by 30% by the year 2025. Nonadherence to chronic medication regimens is common; approximately 43% to 65.5% of patients who fail to adhere to prescribed regimens are hypertensive patients. Nonadherence to medications is a potential contributing factor to the occurrence of concomitant diseases.Objective: This systematic review applied a meta-analytic procedure to investigate the medication nona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…Poor adherence to prescribed medications has been reported among patients with hypertension with a number of factors being implicated to play various roles in this health outcomes [26,37,38]. To the best of our knowledge, no study has reported the associations among patient characteristics, psycho-behavioural factors and medication adherence in male patients with hypertension in Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…Poor adherence to prescribed medications has been reported among patients with hypertension with a number of factors being implicated to play various roles in this health outcomes [26,37,38]. To the best of our knowledge, no study has reported the associations among patient characteristics, psycho-behavioural factors and medication adherence in male patients with hypertension in Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…Medication adherence (MA) can control HBP and its complications more effectively [3] but Medication non-adherence is the most common cause of uncontrolled BP [4]. Despite the critical role of MA in controlling HBP, 30-93% of patients do not take their medication as prescribed [5-7].…”
Section: Introductionmentioning
confidence: 99%
“…Older adults, because of reduced functional abilities, have multiple chronic diseases and polypharmacy that cannot take their medications properly [10]. So they experience more challenges in MA than younger groups [5].…”
Section: Introductionmentioning
confidence: 99%